2019
DOI: 10.1016/j.jjcc.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of stroke volume on prognostic outcome in patients with atrial fibrillation and concomitant heart failure with preserved ejection fraction

Abstract: A B S T R A C TBackground: Atrial fibrillation (AF) can lead to a decrease in stroke volume (SV) despite a preserved left ventricular ejection fraction (LVEF). However, no previous studies have evaluated the prognostic importance of the decreased SV in patients with AF and concomitant heart failure with preserved ejection fraction (HFpEF). Methods: We retrospectively studied the cases of 1520 consecutive patients who had undergone right heart catheterization. HFpEF (New York Heart Association functional class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…However, 12-month difference was neither spread nor attenuated, meaning SV might not be a predictive factor for loss of primary patency after 12 months. Although reduced SV was reported to be significantly associated with cardiac death and hospitalizations due to worsening heart failure at the mean follow-up period of 991 days on the Kaplan-Meier analysis, 23 the current study revealed the incidences of MACE, including cardiac death, and hospitalizations were not significantly different between the 2 groups at 12 months. The impact of SV on prognostic outcome in PAD patients might be established by performing a longer follow-up.…”
Section: Discussioncontrasting
confidence: 74%
“…However, 12-month difference was neither spread nor attenuated, meaning SV might not be a predictive factor for loss of primary patency after 12 months. Although reduced SV was reported to be significantly associated with cardiac death and hospitalizations due to worsening heart failure at the mean follow-up period of 991 days on the Kaplan-Meier analysis, 23 the current study revealed the incidences of MACE, including cardiac death, and hospitalizations were not significantly different between the 2 groups at 12 months. The impact of SV on prognostic outcome in PAD patients might be established by performing a longer follow-up.…”
Section: Discussioncontrasting
confidence: 74%
“…Low stroke volume and low cardiac power has been associated with high short‐term risk across multiple cardiac and noncardiac conditions including cirrhosis, pulmonary hypertension, severe aortic stenosis, acute heart failure, and cardiogenic shock 1,3,6,17‐22 . The present study adds to the existing literature by assessing the long‐term prognostic implications of right heart catheterization‐derived hemodynamic parameters.…”
Section: Discussionmentioning
confidence: 91%
“…Despite the normal LVEF, invasive hemodynamic or echocardiographic measured stroke volume may be impaired in HFpEF patients 29,30 . In our previous study, SVI/S′ was well used for both diagnosis and prognosis in HFpEF 31 .…”
Section: Discussionmentioning
confidence: 96%
“…Despite the normal LVEF, invasive hemodynamic or echocardiographic measured stroke volume may be impaired in HFpEF patients. 29,30 In our previous study, SVI/S 0 was well used for both diagnosis and prognosis in HFpEF. 31 With a cut-off value of 4.08, an AUC of 0.761 for SVI/S 0 was obtained with a sensitivity of 80% and specificity of 64%.…”
Section: Svi/s 0 Performancementioning
confidence: 99%